PSYCHOLOGICAL COMPONENTS OF FORCED MIGRANTS’ POST-TRAUMATIC GROWTH - Яковицька, Лада; Скляр, Вікторія; Кузнєцова, Людмила (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2024)
The state of war continues, so the main focus of the article is on the possibilities of positive changes in the life of Ukrainian forced migrants, which arise due to the challenge of difficult circumstances. Post-traumatic growth is considered as a positive transformation of a person's life, which occurs in the process of adaptation to new circumstances and places of residence, which can generate both a high level of psychological disorder and can serve as catalysts for development. The study aims to empirically investigate and analyze the extent of post-traumatic growth components among forced migrants. It seeks to establish correlations between psychological well-being, resilience, anxiety, and depression levels across various age groups of forced migrants. The research employs the Connor-Davidson Resilience Scale, Hospital Anxiety and Depression Scale, Brief Scale of Anxiety, Depression, and PTSD, and the Posttraumatic Growth Inventory (PTGI) questionnaire as its primary research methods. The results. In the younger group of respondents (20-40 years old), significant inverse correlations of the post-traumatic growth indicator with emotional states of anxiety were established (r=-0.370; p≤0.05); depression (r=-0.342; p≤0.05); the indicator of the Short scale of anxiety, depression and PTSD (r=-0.561; p≤0.01); significant direct correlations of the post-traumatic growth indicator with the Connor-Davidson Resilience Scale (r=0.347; p≤0.05); such correlations were not established for the older group of respondents. Significant direct correlations between the index of posttraumatic growth and internal scales within the PTGI questionnaire: attitude to others, new opportunities, improved relationships, spiritual growth, appreciation of life were established for both age groups. In conclusion, posttraumatic growth emerges as a multifaceted phenomenon that defies simplistic categorization as merely a coping mechanism, cognitive interpretation, psychological adaptation, or well-being outcome. Instead, it likely involves a synthesis of emotional release and cognitive clarity, facilitated by shifts in attitudes towards others, self-regulation, and awareness of new opportunities. These elements enable individuals to assess the fundamental and narrative aspects of their changing experiences, thereby fostering transformative processes among individual migrants.